1984
DOI: 10.1029/jc089ic02p02087
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice structure and biological activity in the Antarctic marginal ice zone

Abstract: Ice cores obtained during October‐November 1981 from Weddell Sea pack ice were analyzed for physical, chemical, and biological parameters. Frazil ice, which is associated with dynamic, turbulent conditions in the water column, predominated (70%). Both floe thickness and salinity indicate ice which is less than 1 year old. Chemical analyses, particularly with regard to the nutrients, revealed a complex picture. Phosphate values are scattered relative to the dilution curve. Nitrate and silicate values are lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 15 publications
2
79
0
Order By: Relevance
“…We also obtained the mean lengths of stratigraphic units, tM, and the mean ratio, R M , of the number of textural units in the top versus the bottom halves of cores. Table I shows the overall fraction of frazil versus congelation growth as seen in the initial study by Cow and others (1987a) and by Clarke and Ackley (1984), as well as in our expeditions. The table indicates clearly that, with the exception of the Winter Weddell Gyre Study in 1989, frazil ice has been more commonly observed than has congelation ice.…”
Section: Field Work/analytical Techniquesmentioning
confidence: 98%
See 1 more Smart Citation
“…We also obtained the mean lengths of stratigraphic units, tM, and the mean ratio, R M , of the number of textural units in the top versus the bottom halves of cores. Table I shows the overall fraction of frazil versus congelation growth as seen in the initial study by Cow and others (1987a) and by Clarke and Ackley (1984), as well as in our expeditions. The table indicates clearly that, with the exception of the Winter Weddell Gyre Study in 1989, frazil ice has been more commonly observed than has congelation ice.…”
Section: Field Work/analytical Techniquesmentioning
confidence: 98%
“…In addition, the 1986 Polarstern study area overlapped that covered by the M. Somov in late winter 1981 (not shown). Results of the sea-ice investigation during the latter expedition are given in Clarke and Ackley (1984). At daily ice stations we obtained a number of ice cores, measured snow and ice thicknesses in at least 100 (and up to 200) mechanically drilled holes and analyzed the surface properties along a standard grid of approximately IS by IS m (Lange, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Convection is either confined in the lowermost, porous sea ice or may develop over the full depth of the ice, with a potential influence on the localization of the communities. Second, dissolved macronutrient concentrations in the ice plotted versus ice salinity lie on a line, in other words, the vertical profiles have the same shape, except when ice microbial communities are active, as indicated by field and laboratory experiments (Clarke and Ackley, 1984;Cota et al, 1987;Meese, 1989;Giannelli et al, 2001;Tison et al, 2008).…”
Section: Sea Ice Biogeochemistrymentioning
confidence: 99%
“…In ice-covered seas, the horizontal distribution of ice microalgae is also known to be patchy (Bunt & Lee 1970, Alexander et al 1974, Horner & Schrader 1982, Garrison et al 1983, McConville & Wetherbee 1983, Clarke & Ackley 1984. However, the factors controlling this patchiness are still under debate.…”
Section: Introductionmentioning
confidence: 99%